ESTUDO LONGITUDINAL DE ADESÃO DE PACIENTES INICIANTES EM TERAPIA ANTIRRETROVIRAL: ESTRATÉGIAS FARMACÊUTICAS ENTRE PESSOAS VIVENDO COM HIV/AIDS - Franca, Patricia de Oliveira (2022)
To achieve the benefits of antiretroviral therapy (ART) and ensure infection control, it is of utmost importance that patients maintain a degree of adherence to therapy higher than 90%. Thus, the aim of this study was to carry out an epidemiological inves